Development of Branding Strengthening Innovations in MSMEs in Surabaya Based on Technopreneurship - Putri Rahma Dayanti; Christina Wulansari; Ni Made Prema Devina Febriyanti; Alyssa Nurrafita Angie; Syfa Anugrahini Setya Nugroho (Dinasti International Journal of Education Management and Social Science, 2025)
The rapid advancement of digital technology has transformed business practices, including those of MSMEs, which are now required to integrate technology into their entrepreneurial activities. This integration is known as technopreneurship. This study aims to identify the strategies employed by culinary MSMEs in strengthening their branding, explore the characteristics of technopreneurship implementation, examine audience responses to digital content, and analyze the influence of such content on branding reinforcement. The research employed a mixed-methods approach, combining quantitative and qualitative techniques. Quantitative data were obtained from 162 respondents through structured questionnaires and analyzed using Spearman’s correlation to examine the relationship between audience responses and variables such as content relevance, reputation, and interaction. Complementary qualitative data were gathered from in-depth interviews with three MSMEs actively engaged in digital branding. Findings revealed significant positive correlations audience responses and the three examined variables. The results indicate that relevant and consistent content, strong reputation, and interactive engagement play key roles in enhancing consumer trust and purchase intentions. Interviews confirmed that MSMEs are increasingly aware of the strategic role of social media, even establishing dedicated teams for content creation. These insights highlight the importance of technopreneurship in expanding market reach and sustaining competitiveness in the digital era.